Design and development of cylindrical composite containers - Zhou, Eden Weijun (Nanyang Technological University, 2023)
This study aimed to optimize the filament winding process of a pressure vessel using ComposiCAD software and a Kuka robotic arm, while also optimizing the curing process of GF-PA6 commingled yarn as the overwrap material for the pressure vessel to ensure that the composite is fully cured. Finite element analysis software ANSYS was utilized to conduct simulations and determine the stress-strain distribution in the laminate sequence configuration. The aim was to identify the maximum internal pressure loading conditions considering the yield strength of the aluminum 6061-T6 liner material. Results showed that with the addition of two helical layers at 30degree and one layer of hoop layer of GF-PA6 commingled yarn composite overwrap helped to increase the maximum internal pressure the vessel could withstand, with an increase of 22.67%. However, this study was limited by assuming isotropic material properties of the composite, which may not accurately reflect the actual behavior of the composite. Future studies can focus on conducting physical testing to obtain the actual material properties of the composite which can aid in providing a more accurate understanding of its behavior.